My Experiences Towards the Way of the Teacher - Vílchez Quesada, Enrique (2011)
This is a biography about my experience in the way of becoming a teacher, about the basic principles of the apprentice after years of experience, about the memories of my first teacher and about the teachings of my best professor. In this tough joumey, many academic and cultural basis are forged which, diluted in dreaming minds, transform themselves in order to determine our humani deals.